The Relationship Between Social Custom and Psychological Health - Mitchell, J. J. (Canadian Journal of Counselling and Psychotherapy, 2012)
Modern psychology has learned a great deal about those aspects of modern society which go contrary to the psychological needs of the individual. However, little is known about two important related concerns: (1) those aspects of modern society which facilitate personal growth and psychological health; and, (2) those psychological disorders which come about primarily because of unexamined rejection of societal norms. A host of new psychological disorders is emerging which stem not from suppression of the individual by his society, but rather from the inability of the person to benefit from those aspects of society which have the potential to contribute to personal health. Our knowledge of psycho- logical disorder will remain limited until we look at both sides of the coin. Thus far, no theoretical analysis of the growth-fostering aspects of society has been undertaken.